Impact of Prognostic Discussions on the Patient-Physician Relationship: Prospective Cohort Study - Fenton, Joshua J; Duberstein, Paul R; Kravitz, Richard L; Xing, Guibo; Tancredi, Daniel J; Fiscella, Kevin; Mohile, Supriya; Epstein, Ronald M (Journal of clinical oncology, 2018)
Purpose Some research has suggested that discussion of prognosis can disrupt the patient-physician relationship. This study assessed whether physician discussion of prognosis is associated with detrimental changes in measures of the strength of the patient-physician relationship. Methods This was a longitudinal cohort study of 265 adult patients with advanced cancer who visited 38 oncologists within community- and hospital-based cancer clinics in Western New York and Northern California. Prognostic discussion was assessed by coding transcribed audio-recorded visits using the Prognostic and Treatment Choices (PTCC) scale and by patient survey at 3 months after the clinic visit. Changes in the strength of the patient-physician relationship were computed as differences in patient responses to The Human Connection and the Perceived Efficacy in Patient-Physician Interactions scales from baseline to 2 to 7 days and 3 months after the clinic visit. Results Prognostic discussion was not associated with a temporal decline in either measure. Indeed, a one-unit increase in PTCC during the audio-recorded visit was associated with improvement in The Human Connection scale at 2 to 7 days after the visit (parameter estimate, 0.10; 95% CI, -0.02 to 0.23) and 3 months after the visit (parameter estimate, 0.18; 95% CI, 0.02 to 0.35) relative to baseline. Standardized effect sizes (SES) associated with an increase of two standard deviations in the PTCC at each time point were consistent with small beneficial effects (SES, 0.14 [95% CI, -0.02 to 0.29] at 2 to 7 days; SES, 0.24 [95% CI, 0.02 to 0.45] at 3 months), and lower bounds of CIs indicated that substantial detrimental effects of prognostic discussion were unlikely. Conclusion Prognostic discussion is not intrinsically harmful to the patient-physician relationship and may even strengthen the therapeutic alliance between patients and oncologists.